Beyond The Domestic Space: The Beauty Of Women In Hijab In The Commercials - Qudratullah; Abd Malik, Ikmal (Musãwa Jurnal Studi Gender dan Islam, 2024)
In advertisements, women are close to the role of models of the products offered. It is because women are considered to have many attractions. This article explores the meaning of the beauty of women wearing the hijab in the Wardah cosmetic advertisement version "Kisah di Balik Cantik: Awal Mimpi ."This advertisement highlights the stories of individual journeys and struggles to achieve authentic and meaningful beauty. This advertisement not only explores the physical aspects of beauty but also promotes messages about beauty that come from within  as well as  motivates personal stories. This can help change the narrow narrative of hijab-wearing women's beauty in the media.  This advertisement features a short story that includes the ability and competence to represent the beauty of women wearing the hijab in making decisions about products, jobs, and partners. This study uses a qualitative approach and Roland Barthes' semiotic as a tool of  analysis. The results of this study indicate that the beauty of women in hijab contains three elements: halal, reasonable, and not excessive. Beauty comes from within, behaves gently, and independently dares to get challenges and work outside the domestic sphere.[Dalam  iklan, perempuan sangat dekat dengan peran model dengan beragam produk yang ditawarkan. Hal ini dikarenakan wanita dianggap memiliki kelebihan dan daya tarik yang banyak dikagumi. Artikel  ini bertujuan untuk menggali makna kecantikan wanita berhijab dalam iklan kosmetik Wardah versi “Kisah di Balik Cantik: Awal Mimpi”. Iklan ini menyoroti cerita perjalanan dan perjuangan individu untuk meraih kecantikan yang autentik dan bermakna. Iklan ini tidak hanya mengeksplorasi aspek fisik kecantikan, tetapi juga mempromosikan pesan tentang kecantikan yang berasal dari dalam dan cerita-cerita pribadi yang memotivasi. Hal ini dapat membantu mengubah narasi yang terkadang sempit tentang kecantikan wanita berhijab dalam media.  Iklan ini menampilkan cerita singkat yang memuat kemampuan dan kompetensi dalam representasi kecantikan perempuan berhijab dalam memilih aspek mengambil keputusan tentang produk, pekerjaan dan pasangan. Penelitian ini menggunakan pendekatan kualitatif  dan semiotika Roland Barthes  sebagai alat analisis. Hasil penelitian ini menunjukkan bahwa kecantikan wanita berhijab mengandung tiga unsur yaitu halal, baik, dan tidak berlebihan. Kecantikan datang dari dalam, berperilaku lembut, dan secara mandiri berani  mengambil tantangan  serta  bekerja di luar ranah domestik]